2015
DOI: 10.7150/jca.12135
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Inhibitor Vaproic Acid Induces Cell Growth Arrest in Hepatocellular Carcinoma Cells via Suppressing Notch Signaling

Abstract: Hepatocellular carcinoma (HCC) is a type of malignant cancer. Notch signaling is aberrantly expressed in HCC tissues with more evidence showing that this signaling plays a critical role in HCCs. In the present study, we investigate the effects of the anti-convulsant drug valproic acid (VPA) in HCC cells and its involvement in modulating Notch signaling. We found that VPA, acting as a histone deacetylase (HDAC) inhibitor, induced a decrease in HDAC4 and an increase in acetylated histone 4 (AcH4) and suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 41 publications
2
48
0
3
Order By: Relevance
“…However, some other reports showed suppressive effects of Notch signaling in HCC cells [9, 12]. The controversy lead us to confirm the role of Notch signaling in HCCs.…”
Section: Resultsmentioning
confidence: 94%
“…However, some other reports showed suppressive effects of Notch signaling in HCC cells [9, 12]. The controversy lead us to confirm the role of Notch signaling in HCCs.…”
Section: Resultsmentioning
confidence: 94%
“…FD-conditioned HCC cells contained a lower level of miR-22 leading to the elevated level of HDAC4, an established oncogenic epigenetic modifier [40, 41], may provide a partial and mechanistic explanation for the association between cancer development and folate deficiency. Added support from a recent study indicated that vaproic acid, a histone deacetylase (HDAC) inhibitor, induced a decrease in HDAC4 and an increase in acetylated histone 4 (AcH4) and suppressed HCC cell growth [42]. …”
Section: Discussionmentioning
confidence: 99%
“…The siRNA targeting HDAC1 in OSCC cell line led to a decrease in cell proliferation and an increase in cell apoptosis (48). It has been shown that HDAC inhibitor could inhibit hepatocellular carcinoma cell proliferation by attenuating NOTCH1 and HES1 expression (49). However, the role of HDAC in Notch signaling in OSCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%